Peroxisome Proliferator-Activated Receptor Gamma in Obesity and Colorectal Cancer: the Role of Epigenetics - Motawi, T. K.; Shaker, O. G.; Ismail, M. F.; Sayed, N. H. (Scientific reports, 2017)
Peroxisome proliferator-activated receptor gamma (PPARγ) is a nuclear receptor that is deregulated in obesity. PPARγ exerts diverse antineoplastic effects. Attempting to determine the clinical relevance of the epigenetic mechanisms controlling the expression PPARγ and susceptibility to colorectal cancer (CRC) in obese subjects, this study investigated the role of some microRNAs and DNA methylation on the deregulation of PPARγ. Seventy CRC patients (34 obese and 36 lean), 22 obese and 24 lean healthy controls were included. MicroRNA levels were measured in serum. PPARγ promoter methylation was evaluated in peripheral blood mononuclear cells (PBMC). PPARγ level was evaluated by measuring mRNA level in PBMC and protein level in serum. The tested microRNAs (miR-27b, 130b and 138) were significantly upregulated in obese and CRC patients. Obese and CRC patients had significantly low levels of PPARγ. A significant negative correlation was found between PPARγ levels and the studied microRNAs. There was a significant PPARγ promoter hypermethylation in CRC patients that correlated to low PPARγ levels. Our results suggest that upregulation of microRNAs 27b, 130b and 138 is associated with susceptibility to CRC in obese subjects through PPARγ downregulation. Hypermethylation of PPARγ gene promoter is associated with CRC through suppression of PPARγ regardless of BMI.